Partnership Pattern between Robusta Coffee Farmers and Mukidi Coffee Home Industry in Gandurejo Village, Temanggung, Central Java - Watemin; Lestari , Esti (New Countryside, 2025)
Temanggung Regency is one of the coffee-producing areas in Indonesia and a leading coffee-producing area in Central Java. In the area, there is the Mukidi Coffee Home Industry, which serves as a center for processing, selling, training, and operating coffee shops in the Temanggung area. A partnership has been established between the Mukidi Coffee Home Industry and Robusta farmers in Gandurejo Temanggung Village to help identify the location of the ongoing partnership, so that by recognizing the strengths and weaknesses of each party, it is hoped that they will be satisfied with the implementation of the partnership. This study aims to examine the partnership pattern applied by the Mukidi Coffee Home Industry in collaboration with Robusta coffee farmers, analyze the relationship between robusta coffee farmers and the Mukidi Coffee Home Industry, and evaluate the final results between robusta coffee farmers and the partnership established with the Mukidi Coffee Home Industry. The method used is a field study, where data were collected through direct observations, in-depth interviews, and documentation. Meanwhile, the data analysis was conducted using qualitative descriptive analysis with a triangulation model. The results of the activity show that there is a common pattern of trading partnership with a mutually beneficial partnership relationship and the end result achieved is mutually beneficial for both parties.